2021
DOI: 10.1099/mgen.0.000493
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics revealed adaptive admixture in Cryptosporidium hominis in Africa

Abstract: Cryptosporidiosis is a major cause of diarrhoeal illness among African children, and is associated with childhood mortality, malnutrition, cognitive development and growth retardation. Cryptosporidium hominis is the dominant pathogen in Africa, and genotyping at the glycoprotein 60 (gp60) gene has revealed a complex distribution of different subtypes across this continent. However, a comprehensive exploration of the metapopulation structure and evolution based on whole-genome data has yet to be performed. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…In particular, we show that the orthologs of mucin encoding protein CHUDE2_430 and a hypothetical protein CHUDE6_5270 are consistently identified as being under positive selection (Ka/Ks > 1) in the evolution of C. hominis subspecies. These findings corroborate similar conclusions made in previous studies on C. hominis in Africa 19 , and between C. parvum parvum zoonotic vs C. parvum anthroponosum subspecies 14 . Altogether, these data strongly suggest that these genes are directly related to invasion and human-host adaptation, presenting potential targets for diagnostics to discriminate the subspecies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, we show that the orthologs of mucin encoding protein CHUDE2_430 and a hypothetical protein CHUDE6_5270 are consistently identified as being under positive selection (Ka/Ks > 1) in the evolution of C. hominis subspecies. These findings corroborate similar conclusions made in previous studies on C. hominis in Africa 19 , and between C. parvum parvum zoonotic vs C. parvum anthroponosum subspecies 14 . Altogether, these data strongly suggest that these genes are directly related to invasion and human-host adaptation, presenting potential targets for diagnostics to discriminate the subspecies.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we examined the evolutionary genomics of a human associated parasite, C. hominis, studying whole genome sequence data from over a hundred C. hominis isolates from 16 low-and high-income countries across five continents. We thereby expand on earlier studies that analysed the population genomics of C. hominis in Africa 19 , and population genetic studies that used selected genomic markers 25 . In particular, we examined the evolution of two main subtype populations i.e., whole genome sequences with gp60 subtype IbA10G2, versus those that did not contain this particular gp60 sequence ("not-IbA10G2").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If two or more Cryptosporidium strains infect a single host, recombination can rapidly generate evolutionary novelty. Several recent whole genome sequencing studies [9][10][11] have explored the evolutionary genetics of Cryptosporidium. For example, a study of C. hominis in children from a Bangladeshi community found high levels of genomic recombination, possibly due to the high transmission rate and likelihood of mixed infections [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of C. hominis in children from a Bangladeshi community found high levels of genomic recombination, possibly due to the high transmission rate and likelihood of mixed infections [9]. Tichkule et al [10] found evidence of population admixture between distinct geographical lineages of C. hominis in Africa, showing that these lineages have been exchanging genetic information through recombination.…”
Section: Introductionmentioning
confidence: 99%